Differential gene regulation in selected lines for high and low sperm production in male guppies. Issue 4 (25th February 2020) - Cattelan, Silvia; Vidotto, Michele; Devigili, Alessandro; Pilastro, Andrea; Grapputo, Alessandro
Abstract: In species where females mate with more than one male during the same reproductive event, males typically increase the number of sperm produced to boost their fertilization share. Sperm is not limitless, however, and theory predicts that their production will come at the cost of other fitness‐related traits, such as body growth or immunocompetence, although these evolutionary trade‐offs are notoriously difficult to highlight. To this end, we combined artificial selection for sperm production with a transcriptome analysis using Poecilia reticulata, a fish characterized by intense sperm competition in which the number of sperm transferred during mating is the most important predictor of fertilization success, yet sperm production is highly variable among males. We compared the brain and testes transcriptome in male guppies of lines artificially selected for high and low sperm production by identifying pivotal differentially expressed gene sets that may regulate spermatogenesis and immune function in this species. Despite the small differences in single genes' expression, gene set enrichment analysis showed coordinated gene expression differences associated with several pathways differentially regulated in the two selection lines. High sperm production males showed an upregulation of pathways related to immunosuppression and development of spermatozoa indicating a possible immunological cost of sperm production. Abstract : We compared the brain and testes transcriptome of male guppies ( Poecilia reticulata ) previously artificially selected for high and low sperm production to identify pivotal differentially expressed gene sets that may regulate spermatogenesis and immune function in this species. High sperm production males showed an upregulation of gene pathways related to immunosuppression and the development of spermatozoa. Altogether, these results suggest that producing high sperm numbers may come at a cost for immunocompetence and sperm quality.